EXPLORATION DETERMINATION OF PATCHOULI PLANTING LOCATION (CASE STUDY: GARUT REGENCY) - DWI PRATIWI (NIM : 12813017), YUKI
Patchouli is one of high prospect plants in Indonesia due to its various profitable special qualities. In cultivating patchouli, it is necessary to classify the conformity of climate as well as the land to manifest the improvement of efficiency production. This research attempts to map potential zones for patchouli plants in Garut Regency in accordance to the conformity of agroclimate and determining the effectiveness planting times which is based on the calculation of onset monsoon, as well as to calculate the productivity value of patchouli which is analyzed based on several meteorology phenomena. In this research the determination of effective planting time based on the calculation of onset monsoon is determined by using criteria Australian Monsoon Rainfall Index (AMRI) DELTA-2 which prescribes the occurrence of onset when the 5-day running mean of rainfall exceeds the value of 150% Mean Annual Cycle (MAC) and the difference between 150% MAC and MAC itself exceeds 1 mm. By using this criterion, the determination of effective planting time for patchouli plants in Garut Regency can be determined. Then, potential zoning maps and effective cultivation time for patchouli plants can be resulted. In addition, this study also discusses the influence of meteorological phenomena on the value of patchouli plant productivity in Garut Regency. Garut regency classified to B – Climate regarding to Schmidt – Ferguson, thus are suitable climate for patchouli cultivation. The analysis of agroclimate compatibility reveals that there are as many as areas that suitable (S2) for cultivating patchouli of 19 sub-regencies that sit on 602, 89 km2 area which are spread over 4 potential zone areas. Based on the calculation of AMRI DELTA-2 method, the suitable planting plan can be started on the middle of September. The productivity of patchouli in 1999 to 2013 got fluctuation and it was influenced by atmospheric dynamics phenomenon such as El Nino South Oscillation (ENSO) and Madden Julian Oscillation (MJO). In a year when El Nino happened, the number of productivity decreased. Whilst, in a year when La Nina happened the number of productivity tent to increase.